1981
DOI: 10.1128/iai.34.1.234-240.1981
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemotaxis in the association of motile bacteria with intestinal mucosa: in vivo studies

Abstract: In vivo loops were prepared in the small intestine of rabbits and injected with mixtures of Vibrio cholerae and polystyrene spheres (1.1-tim diameter). The loops were removed and frozen after 15 min and then sectioned in a cryostat. The locations of particles and vibrios were determined microscopically. The vibrio/ particle ratio was unity in the lumen of the loops, but increased 10-fold in the deep intervillous spaces, indicating active invasion of the mucus gel by the chemotactic parent strain. Motile nonche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
2
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(89 citation statements)
references
References 19 publications
1
85
2
1
Order By: Relevance
“…It has been demonstrated using FISH that growth of both commensal and pathogenic E. coli strains mainly takes place in the mucus layer of the large intestine (Poulsen et al, 1994;Moller et al, 2003). Other enteropathogens, such as Salmonella enterica serovar Typhimurium (S. Typhimurium), Citrobacter rodentium, and V. cholerae were shown to grow in the mucus layer (Freter et al, 1981;Stecher et al, 2004Bergstrom et al, 2010). Escherichia coli genes and pathways induced upon growth in cecal mucus include catabolism of the major mucin-derived sugars N-acetylglucosamine (NAG), N-acetylneuraminic (sialic) acid, glucosamine, fucose and ribose, tryptophan, threonine, serine, aspartate, and phosphatidylethanolamine (Chang et al, 2004).…”
Section: The Mucus Layer Paradox: Barrier Function and Nutrient Sourcementioning
confidence: 99%
“…It has been demonstrated using FISH that growth of both commensal and pathogenic E. coli strains mainly takes place in the mucus layer of the large intestine (Poulsen et al, 1994;Moller et al, 2003). Other enteropathogens, such as Salmonella enterica serovar Typhimurium (S. Typhimurium), Citrobacter rodentium, and V. cholerae were shown to grow in the mucus layer (Freter et al, 1981;Stecher et al, 2004Bergstrom et al, 2010). Escherichia coli genes and pathways induced upon growth in cecal mucus include catabolism of the major mucin-derived sugars N-acetylglucosamine (NAG), N-acetylneuraminic (sialic) acid, glucosamine, fucose and ribose, tryptophan, threonine, serine, aspartate, and phosphatidylethanolamine (Chang et al, 2004).…”
Section: The Mucus Layer Paradox: Barrier Function and Nutrient Sourcementioning
confidence: 99%
“…The presence of this organism in aquatic environments contributes to endemic disease, and the evolution of new pathogenic strains provides the potential for epidemic, and even pandemic, spread (Mel and Mekalanos, 1996). The relationship between V. cholerae motility and pathogenesis has been studied for many years (Fretter et al, 1981); however, a well-defined role for motility in this context still remains uncertain (Richardson, 1991;Gardel and Mekalanos, 1996). Some interesting links between the expression of virulence determinants and motility have been found recently.…”
Section: Glowing Squid Septic Trout and Aquatic Vibriosmentioning
confidence: 99%
“…However, these events are also viewed as virulence properties that may favour adherence to or penetration into eukaryotic cells (Finlay and Falkow, 1989;Salyers and Whitt, 1994;Allison et aL, 1992). In the intestine, these properties would seem crucial for enteric pathogens such as Vibrio cholerae, Campylobacter jejuni, Helicobacter pylori and Salmonella typhimurium to swim across the mucus layer in the gastrointestinal tract in order to reach suitable sites for colonization and invasion (Freter et aL, 1981;Carsiotis et aL, 1984;Guentzel and Berry, 1975;Hazell etaL, 1986;Weinstein et aL, 1984;Eaton et aL, 1992). However, other workers have shown that the lack of flagella and motility does not affect the virulence of mouse pathogens (McCormick et aL, 1990;Lockman and Curtis, 1990).…”
Section: Introductionmentioning
confidence: 99%